Behavior and Flexural Strength of Ferrocement One Way Slabs with Square Openings. - Saeed, Jalal A.; Mohammad, Payman H.; Aziz, Ibrahim H. (Sulaimani Journal for Pure and Applied Sciences, 1997)
The paper presents experimental results of nine enforcement one way slabs with openings subjected to two point loads taking into consideration number of mesh layers and size of the openings as variables. The results showed that by increasing number of mesh layers the slabs' flexural strength increased and size of the openings have negative effect on flexural strength of the slabs. Finally empirical equations are suggested to calculate cracking and ultimate loads in terms of width of the openings and number of mesh layers and the results showed good agreement with experimental values.